Sistem surveilans dan respons / Deni Kurniadi Sunjaya, Dewi Marhaeni Diah Herawati ; editor, Genis Ginanjar Wahyu...[et al] ; ilustrasi, M. Mukhlis F.A. - DENI KURNIADI SUNJAYA; Dewi Marhaeni Diah Herawati; Genis Ginanjar Wahyu; Mukhlis F.A., M. (Sagung Seto, 2012)
ix, 102 hlm. : ilus. ; 23 cm [3 eks.]